2006
DOI: 10.1097/01.mao.0000226315.27811.c8
|View full text |Cite
|
Sign up to set email alerts
|

Familial Ménière's Disease in Five Generations

Abstract: The pattern of inheritance suggested that familial MD was autosomal dominant and exhibited incomplete expression of inner ear symptoms in some affected members. The decreasing age at onset of disease with succeeding generations could indicate anticipation. None of the hitherto-known DFNA loci, which has phenotypes bearing some resemblance to MD, had haplotypes in common with this large family affected by MD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 16 publications
0
22
1
Order By: Relevance
“…Although anticipation has been described in several FMD families [7,8,18], only two families with clearly diminishing age at onset possibly implying anticipation was seen in this study. It is possible that anticipation phenomenon in MD is nothing more than a bias caused by the increase in health-care availability among generations, as we have suggested earlier [11].…”
Section: Discussioncontrasting
confidence: 75%
“…Although anticipation has been described in several FMD families [7,8,18], only two families with clearly diminishing age at onset possibly implying anticipation was seen in this study. It is possible that anticipation phenomenon in MD is nothing more than a bias caused by the increase in health-care availability among generations, as we have suggested earlier [11].…”
Section: Discussioncontrasting
confidence: 75%
“…Previous reports have demonstrated that 7% of all patients with MD have an affected family member (10). Through larger studies, familial MD has been identified as an autosomal dominant disorder with approximately 60% penetrance (21,37). Many candidate genes have been studied in the development of MD, but no specific gene mutation has been identified.…”
Section: Discussionmentioning
confidence: 97%
“…The 5.4% in first-degree relatives is probably reasonably accurate. Two further recent reports 26,27 describe medium-to-large multiply-affected families.…”
Section: Introductionmentioning
confidence: 99%